Optimizing nutrient solution for vegetative growth of Dendrobium Tubtim Siam and Phalaenopsis Taisuco Swan through plant tissue nutrient balance estimation - Costa, Milton G. [UNESP]; Mantovani, Cibele [UNESP]; de Mello Prado, Renato [UNESP] (Springer Nature, 2024)
Background: Orchids are grown without soil in many regions of the world, but there is a lack of studies to define the balanced and adequate nutrient solution for their cultivation, mainly in the vegetative growth phase. Therefore, this paper aims to evaluate the optimal concentration of the nutrient solution based on the proposal by Hoagland and Arnon (1950) in the vegetative growth phase capable of increasing the nutrient contents, growth, and dry matter production of Dendrobium Tubtim Siam and Phalaenopsis Taisuco Swan. In addition, this paper aims to estimate a new nutrient solution from the optimal nutrient contents in the dry matter of these orchid species to be used in the vegetative growth phase. Results: Nutrient contents, growth, and dry matter production increased as the nutrient solution concentration increased up to an average concentration of 62 and 77% for D. Tubtim Siam and P. Taisuco Swan, respectively. We found that the Hoagland and Arnon solution presented a group of nutrients with concentrations above the requirement for P. Taisuco Swan (nitrogen, phosphor, calcium, and sulfur) and D. Tubtim Siam (phosphor, calcium, magnesium, and sulfur), while other nutrients in the solution did not meet the nutritional demand of these orchid species, inducing nutritional imbalance in the vegetative growth phase. Conclusion: We conclude that using a balanced nutrient solution created specifically for each orchid species in vegetative growth might favor their sustainable cultivation by optimizing the use of nutrients in the growing medium.
Keywords: Dendrobium Tubtim Siam; Nutritional balance, Orchidaceae; Phalaenopsis Taisuco Swan; Plant nutrition